Comparative Treatment Failure Rates of Respiratory Fluoroquinolones or β-Lactam + Macrolide Versus β-Lactam Alone in the Treatment for Community-Acquired Pneumonia in Adult Outpatients: An Analysis of a Nationally Representative Claims Database. Issue 39 (September 2015) - Lee, Meng-Tse Gabriel; Lee, Shih-Hao; Chang, Shy-Shin; Chan, Ya-Lan; Pang, Laura; Hsu, Sue-Ming; Lee, Chien-Chang
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: No comparative effectiveness study has been conducted for the following 3 antibiotics: respiratory fluoroquinolone, β-lactam, and β-lactam + advanced macrolide. To gain insights into the real-world clinical effectiveness of these antibiotics for community-acquired pneumonia in adult outpatients, our study investigated the treatment failure rates in 2 million representative participants from the National Health Informatics Project (NHIP) of Taiwan. A new-user cohort design was used to follow NHIP participants from January 2000 until December 2009. Treatment failure was defined by either one of the following events: a second antibiotic prescription, hospitalization due to CAP, an emergency department visit with a diagnosis of CAP, or 30-day nonaccident-related mortality. From 2006 to 2009, we identified 9256 newly diagnosed CAP outpatients, 1602 of whom were prescribed levofloxacin, 2100 were prescribed moxifloxacin, 5049 were prescribed β-lactam alone, and 505 were prescribed advanced macrolide + β-lactam. Compared with the β-lactam-based regimen, the propensity score-matched odds ratio for composite treatment failure was 0.81 (95% CI, 0.67–0.97) for moxifloxacin, 1.10 (95% CI, 0.90–1.35) for levofloxacin, and 0.95 (95% CI, 0.67–1.35) for macrolide +β-lactam. Moxifloxacin was associated with lower treatment failure rates compared with β-lactam alone, or levofloxacin in Taiwanese CAP outpatients. However, due to inherent limitations in our claims database, more randomized controlled trials are required before coming to a conclusion on which antibiotic is more effective for Taiwanese CAP outpatients. More population-based comparative effectiveness studies are also encouraged and should be considered as an integral piece of evidence in local CAP treatment guidelines.